2017
DOI: 10.1136/bjophthalmol-2017-311249
|View full text |Cite
|
Sign up to set email alerts
|

Keratolimbal allograft for limbal stem cell deficiency after severe corneal chemical injury: a systematic review

Abstract: CRD42017054733.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…A recent systematic review on clinical outcomes of keratolimbal allograft in LSCD after severe corneal chemical injury evaluated six nonrandomized, controlled studies and reported a best corrected visual acuity ≥ 20/200 in 69% (20/29) of the eyes at the last follow-up examination (mean follow-up range 6.2–114 months). The authors concluded that the quality of the evidence to support the use of keratolimbal allograft in LSCD is low and further, standardized studies with long-term follow-up are needed [ 89 91 ]. In addition, different studies used different immunosuppression regimens after keratolimbal allograft; in fact, even if most studies used systemic cyclosporine, there is not a standardized immunosuppressive regimen for keratolimbal allograft [ 91 ].…”
Section: Clinical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review on clinical outcomes of keratolimbal allograft in LSCD after severe corneal chemical injury evaluated six nonrandomized, controlled studies and reported a best corrected visual acuity ≥ 20/200 in 69% (20/29) of the eyes at the last follow-up examination (mean follow-up range 6.2–114 months). The authors concluded that the quality of the evidence to support the use of keratolimbal allograft in LSCD is low and further, standardized studies with long-term follow-up are needed [ 89 91 ]. In addition, different studies used different immunosuppression regimens after keratolimbal allograft; in fact, even if most studies used systemic cyclosporine, there is not a standardized immunosuppressive regimen for keratolimbal allograft [ 91 ].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The authors concluded that the quality of the evidence to support the use of keratolimbal allograft in LSCD is low and further, standardized studies with long-term follow-up are needed [ 89 91 ]. In addition, different studies used different immunosuppression regimens after keratolimbal allograft; in fact, even if most studies used systemic cyclosporine, there is not a standardized immunosuppressive regimen for keratolimbal allograft [ 91 ]. In most cases, the interpretation of the results has been hampered either by the lack of a proper genetic evaluation of the presumptive long-term engraftment of allogeneic limbal grafts or by the inadequate length of the follow-up.…”
Section: Clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with bilateral LSCD, limbal stem cells may be harvested from immediate family members as a livingrelated conjunctival-limbal allograft (lr-CLAL), cadaveric eyes as a keratolimbal allograft (KLAL) or allogenic cultivated limbal epithelial transplantation (allo-CLET) [93,94]. These allogeneic transplants obviously require systemic immune suppression.…”
Section: Management Of Chronic Complicationsmentioning
confidence: 99%
“…A recent systemic review looked at studies in which KLAL was done for chemical injury induced total LSCD. Eightynine percent underwent simultaneous or subsequent penetrating keratoplasty [94]. Median follow-up for 29 eyes was 42 months (range: 6.2-114 months), and 69% had BCVA ≥20/200 at last follow-up.…”
Section: Management Of Chronic Complicationsmentioning
confidence: 99%